Relatnions between the legal system and other legal notions - Хаустова, М. Г. (Problems of legality, 2015)
The article has analysed the notion of legal system, its relathionship with such legal phenomena as legalsuperstructure the mechanism of legal control, legal reality and legal life, The author has determined their common features, strycture and mutual in fluence of legal phenomena on each other and on the social relations as a whole.